Talent management process in Asia: a multiple case study. Issue 7 (17th October 2018) - Li, Jessica; Hedayati-Mehdiabadi, Amir; Choi, Jeonghwan; Wu, Feng; Bell, Allison
Abstract : Purpose: The purpose of this study is to examine talent management process in a region that has been influenced by Eastern culture. Design/methodology/approach: This research is a multiple case study of six MNCs in Asia. Cross-cases analysis was used to reveal differences and similarities. The data were collected through phone interviews with HR managers and written communications as well as organizations' websites. Findings: The studied companies were dealing with several challenges regarding talent management process, including challenges of attracting and retaining talent, tension between subsidiaries and headquarters, tension between high potentials and non-high potentials and tension between generations. These companies' strategies for addressing these challenges were also identified and discussed. Originality/value: This paper revealed talent management orientation, the approach toward and definition of talent and context-specific issues regarding talent management of the selected companies in a region in which this topic has not been sufficiently studied in the past.